Exploring PANoptosis in head and neck cancer: A novel approach to cancer therapy - Li Wang; Baisheng Lin; Feixiang Wang; Zili Dai; Guofeng Xie; Jian Zhang (Ecotoxicology and Environmental Safety)
PANoptosis is a newly discovered complex programmed cell death (PCD) form. In the field of cancer research, PANoptosis is involved in multiple cell death pathways that affect tumor cell survival, proliferation, and response to treatment, serving as an innovative strategy for cancer therapy. Endocrine-disrupting chemicals (EDCs) impact the endocrine system, including cancer. However, research on their influence on head and neck carcinoma (HNSC) through PANoptosis genes remains limited. This study utilises transcriptomic and clinical data related to HNSC from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. We developed a risk model based on PANoptosis-related genes through LASSO Cox regression analysis. Finally, we utilized a Sankey diagram to depict the relationships between EDCs and key genes, identifying DSCAM, IL-6, and SYCP2 as critical predictors of HNSC PANoptosis. These essential genes identified 214 EDCs potentially influencing HNSC, including 3 (Aroclor 1242, Pentachlorobenzene, and Propanil) previously unreported to HNSC. These findings elucidate novel relationships between PANoptosis-related genes mediated by EDCs and the pathogenesis of HNSC.